Effect of Pulse Shape and Polarization for Radiation Pressure Ion Acceleration - Nasreen Ansari; Krishna Kumar Soni (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Radiation pressure dominant (RPD) regime represents a highly efficient mechanism for ion acceleration, where the momentum transfer from an ultra-intense laser pulse to an overdense plasma target is governed primarily by radiation pressure. In this study, we investigate how the shape and polarization of laser pulses influence the dynamics of ion acceleration within the RPD regime. The study focuses on the impact of two key laser pulse characteristics—its profile (comparing Gaussian and Hyperbolic Secant shapes) and its polarization state (whether circular or linear)—on the efficiency of ion acceleration. The paper investigates the comparative effectiveness of energy and momentum transfer into plasma ions. The implications of these findings are significant for the advancement of laser-driven ion acceleration applications such as cancer therapy, nuclear fusion, and materials science etc.